Quantitative-Qualitative Discussion: The Emerging Paradigm as Combination Approaches (Shaheed Smriti Journal, 2024)
Using a comprehensive orientation of the research idea from the ontology to the epistemology basis, this article examines the distinctions between qualitative and quantitative social research approaches. The main foundation of this work is a comprehensive review of the body of research on both qualitative and quantitative methods. This analysis makes it abundantly evident that the qualitative and quantitative approaches are different from one another. These distinctions are found in the various research layers. The mix-method approach is the best alternative strategy for social research, according to the discussion of qualitative and quantitative approaches and their advantages and disadvantages. Therefore, the mix-method not only offers the advantages of both the quantitative and qualitative approaches, but it also resolves the current controversy and reduces their drawbacks.